2020
DOI: 10.1111/plb.13080
|View full text |Cite
|
Sign up to set email alerts
|

Epiphyte associations and canopy soil volume: nutrient capital and factors influencing soil retention in the canopy

Abstract: Canopy soil (CS) volume reflect epiphyte community maturity, but little is known about the factors that retain CS or species succession within it. Humus fern species (e.g. Phlebodium areolatum) appear capable of retaining CS.• In ten Quercus spp. we sampled 987 epiphyte mats to examine the role of the common epiphyte species and crown traits determining CS volume, in order to infer successional stages and identify pioneer and late successional species. Branch traits (height, diameter and slope), CS volume and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(33 citation statements)
references
References 55 publications
(123 reference statements)
1
32
0
Order By: Relevance
“…Only the gradient of precipitation influenced the composition of AG epiphytes, but not their richness, with some species occurring in particular sites. For example, Codonanthe Competition or facilitation (nurse plants) interactions limit or promote, respectively, the establishment of epiphyte species in the canopy (Jian et al, 2013;Chaves & Rossatto, 2020;Victoriano-Romero et al, 2020). The network analyses showed that the most frequent true AG epiphytes in the sites were also the most central in the regional network, while the non-true AG epiphytes lack importance in the network, suggesting that they are opportunistic (Kaufmann & Maschwitz, 2006) or even parasitic (Davidson, 1988) species that take advantage of the nutrients of the ant-garden substrate (Blüthgen et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Only the gradient of precipitation influenced the composition of AG epiphytes, but not their richness, with some species occurring in particular sites. For example, Codonanthe Competition or facilitation (nurse plants) interactions limit or promote, respectively, the establishment of epiphyte species in the canopy (Jian et al, 2013;Chaves & Rossatto, 2020;Victoriano-Romero et al, 2020). The network analyses showed that the most frequent true AG epiphytes in the sites were also the most central in the regional network, while the non-true AG epiphytes lack importance in the network, suggesting that they are opportunistic (Kaufmann & Maschwitz, 2006) or even parasitic (Davidson, 1988) species that take advantage of the nutrients of the ant-garden substrate (Blüthgen et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the decomposition of dead organic matter is influenced by temperature and moisture (Bradford et al, 2016; Prescott et al, 2000). Therefore, arboreal soil is most abundant in the inner crown, where humidity is relatively high and the physical structures of the tree support its accumulation (Köhler et al, 2007; ter Steege & Cornelissen, 1989; Veneklaas et al, 1990; Victoriano‐Romero et al, 2020). At a stand level, both substrate types are particularly abundant in tropical montane cloud forests and subtropical and temperate rain forests (Gotsch et al, 2016).…”
Section: Ecology Of Accidental Epiphytismmentioning
confidence: 99%
“…Suspended soils along tree trunks and branches retain nutrients and water essential for the development of epiphytic plants [26] that directly depend on these limited pools of available nutrients [27]. These plants are morphologically and physiologically adapted to facilitate the accumulation of leaf litter and water and to maximize atmospheric and invertebrate-mediated delivery of nutrients [15,28,29] in the physically harsh and variable environmental conditions that prevail within the canopy [30].…”
Section: Introductionmentioning
confidence: 99%
“…Epiphytes have evolved numerous remarkable adaptations to facilitate nutrient uptake. For example, certain members of the Bromeliaceae family form water and litter-storing phytotelmata and take up nutrients through leaf-absorbing trichomes [29,34,35], whilst Asplenium ferns intercept falling leaf litter, which is then stored as organic matter adjacent to the roots [27,36]. For both epiphytes, this accumulation of leaf litter leads to the formation of organic matter or epiphyte-associated soils that harbor characteristic levels of microbial diversity [37,38].…”
Section: Introductionmentioning
confidence: 99%